Life cycle and reproductive capacity of Rotylenchulus reniformis - ZHANG Yan; SHI Hong-li; GUO Kai; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版)
To find out life cycle and reproductivity of Rotylenchulus reniformis, soybean seedlings were inoculated with second stage juveniles (J2) of R. reniformis, and the parasitic situation and development of R. reniformis on the soybean roots were observed systematically by the periodical sampling and using NaClO-acid fuchsin-glycerin staining technique. At the same time, the reproduction of R. reniformis on the soybean including the number of the nematodes in soil, females and egg masses of root system, eggs per egg mass, and fresh mass and dry mass of soybean shoots and roots were measured at 80 days after inoculation with 10, 100, 1 000 and 10 000 J2·pot-1, and all statistical analysis were conducted with SAS version 9.0. The results indicated that life cycle of R. reniformis was about 27 d at (27±2)℃ for soybean. The numbers of the nematodes in soil, eggs per egg mass, final nematode numbers and reproductive factors were significantly different after 80 days of inoculation with different inoculum levels. The reproductive factors, eggs per egg mass decreased with an increase in the inoculum levels, whereas the others were increased with increase of the inoculum levels. The highest reproductive factor was about 48 times of the lowest one, with the highest and the lowest being 140.4 and 2.9, respectively. The growth of soybean was affected, and its fresh and dry mass was decreased with increase of the inoculum levels.